Resting state hyperconnectivity of the default mode network in schizophrenia and clinical high-risk state for psychosis - Sasabayashi, Daiki; Takahashi, Tsutomu; Takayanagi, Yoichiro; Nemoto, Kiyotaka; Ueno, Maya; Furuichi, Atsushi; Higuchi, Yuko; Mizukami, Yuko; Kobayashi, Haruko; Yuasa, Yusuke; Noguchi, Kyo; Suzuki, Michio (Cerebral cortex (New York, N.Y. 1991), 2023)
Abstract Disrupted functional connectivity (FC) of the default mode network (DMN) may have a pathophysiological role in schizophrenia. However, functional magnetic resonance imaging (fMRI) of the DMN in schizophrenia patients has shown inconsistent results. It also remains unclear whether individuals with at-risk mental state (ARMS) have an altered DMN connectivity and whether it is related to clinical characteristics. This fMRI study examined resting-state FCs of the DMN and its relevance to clinical/cognitive variables in 41 schizophrenia patients, 31 ARMS individuals, and 65 healthy controls. Compared with controls, schizophrenia patients had significantly increased FCs within the DMN and between the DMN and diverse cortical areas, whereas ARMS patients had increased FCs only between the DMN and occipital cortex. FC of the lateral parietal cortex with superior temporal gyrus was positively correlated with negative symptoms in schizophrenia, whereas FC of that with interparietal sulcus was negatively correlated with general cognitive impairment in ARMS. Our findings suggest that increased FCs between the DMN and visual network commonly seen in schizophrenia and ARMS subjects may reflect a network-level disturbance representing a general vulnerability to psychosis. In addition, FC changes related to the lateral parietal cortex may underpin clinical characteristics of ARMS and schizophrenia subjects.